2011
DOI: 10.1159/000330428
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neutrophil Gelatinase-Associated Lipocalin Measured on Admission to the Intensive Care Unit Accurately Discriminates between Sustained and Transient Acute Kidney Injury in Adult Critically Ill Patients

Abstract: Background: First we aimed to evaluate the ability of neutrophil gelatinase-associated lipocalin (NGAL) and cystatin-C (CyC) in plasma and urine to discriminate between sustained, transient and absent acute kidney injury (AKI), and second to evaluate their predictive performance for sustained AKI in adult intensive care unit (ICU) patients. Methods: A prospective cohort study of 700 patients was studied. Sample collection was performed over 8 time points starting on admission. Results: After exclusion 510 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…21 Similarly, a recent study in a cohort of 45 sepsis patients showed the parameter uNGAL was a good diagnostic marker for AKI development, but not for AKI severity, when it was recorded after a rise in SCr had occurred. [22][23][24] In our study, the peak uNGAL was found to be correlated with the laboratory and clinical parameters, reflecting the severity of septic AKI (Figure 1). The diagnostic accuracy for septic AKI was highest with the peak uNGAL, as compared with the admission uNGAL (Figure 2).…”
Section: Discussionsupporting
confidence: 51%
“…21 Similarly, a recent study in a cohort of 45 sepsis patients showed the parameter uNGAL was a good diagnostic marker for AKI development, but not for AKI severity, when it was recorded after a rise in SCr had occurred. [22][23][24] In our study, the peak uNGAL was found to be correlated with the laboratory and clinical parameters, reflecting the severity of septic AKI (Figure 1). The diagnostic accuracy for septic AKI was highest with the peak uNGAL, as compared with the admission uNGAL (Figure 2).…”
Section: Discussionsupporting
confidence: 51%
“…We performed a post-hoc analysis on a prospectively gathered biomarker dataset from a previously published cohort [12,13]. The institutional review board of Erasmus MC, University Medical Center Rotterdam, The Netherlands, approved the initial study.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 In our study, ten patients (11.4%) did not progress beyond the AKIN stage II, indicating that some patients in this group probably had functional renal failure (transient AKI or prerenal azotemia) without any significant renal tubular injury. The incidence of transient AKI was similar to the study done by Hoste et al 27 (18%).…”
mentioning
confidence: 51%